Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2023)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates.<br

Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2024)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates. Research Highlights: Enabling cryo-preparation of (nano)particles for the atom probe. Characterization of surface and bulk elemental distribution of GaPt model SCALMS.
CRIS-Team Scopus Importer:2024-02-16
Keywords: atom probe tomography; catalyst particles; cryo preparation; nanoparticles